Cambridge lower secondary English learner's book 7 - Elsdon, Graham (United kingdom : Cambridge university press, 2021)
The Cambridge Lower Secondary English Learner's Book 7 is designed for students in the 7th grade, providing a comprehensive approach to language development. The book focuses on enhancing reading, writing, listening, and speaking skills. Key themes explored include a variety of fiction and non-fiction texts, emphasizing vocabulary building, comprehension strategies, grammar practice, and critical thinking. It encourages students to understand diverse perspectives through engaging stories and exercises.
Keywords: English : Textbook